2018
DOI: 10.1111/phpp.12412
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variants associated with skin photosensitivity in a southern European population from Spain

Abstract: MC1R, IRF4, HERC2 and SLC45A2 play a significant role in skin sensitivity to sunlight in the Spanish population. Moreover, interaction among these four loci seems to modulate the ability of the skin to respond to UV radiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…The ancestral C allele appears to have a protective effect on skin sensitivity to the sun. (Hernando et al, 2018). Soejima et al described that in European populations the allele G is found at high frequency and the allele C at low frequency, the opposite happens in South Africa populations, the ancestral allele C is more recurrent and allele G appears at very low frequencies (Soejima & Koda, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The ancestral C allele appears to have a protective effect on skin sensitivity to the sun. (Hernando et al, 2018). Soejima et al described that in European populations the allele G is found at high frequency and the allele C at low frequency, the opposite happens in South Africa populations, the ancestral allele C is more recurrent and allele G appears at very low frequencies (Soejima & Koda, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…These findings are aligned with the theory of vitamin D synthesis. Which proposes that light skin is a feature selected to compensate for the lower solar incidence in populations living far from the Equator [ 42 ] and with increased ability of the skin to respond to ultra violet (UV) radiation [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover α-MSH/MC1R signaling is a potent anti-inflammatory pathway and has been shown to promote anti-melanoma immunity (27). Human MC1R genetics variants are associated with sunlight sensitivity (28), and altered expression of MC1R have been associated with red hair and skin cancer risk (29).…”
Section: Discussionmentioning
confidence: 99%